Computational implementation of indices of power - Aguirre, Jesús Francisco (2000)
In this paper we present algorithms and computational implementation of the Shapley Value and Banzhaf– Coleman Index of Power. Both indices describe the real power of the coalitions involved in strategic interactions. The system allows the study of complex Electoral Applications. The data input can be done in two different ways: by considering all the possible coalitions, or only the basic coalitions (political parties, sectorial groups, etc.). The system also allows to introduce restrictions (incompatibilities) among some coalitions. We present some applications for computing the Electoral Power in the election of authorities in Universidad Nacional de San Luis. We describe the client–server design and the implementation of these tools, using the languages C and Tcl/Tk. The server program is written in C and requires Linux. The Client Program is written in Tcl/Tk with namespace mechanism and it supports Linux and Windows.